Language Disorder In The Main Character Of Tyson’s Run Movie - Novita Matildis Stefania Ersam; I Made Rajeg; Anak Agung Sagung Shanti Sari Dewi (FKIP, Universitas Palangka Raya, 2023)
This at finding out the types of language disorders and finding out the kinds of language therapy given to the main character of Tyson’s Run movie. The data was taken from the Tyson’s Run movie. The method used in collecting the data was documentation and note-taking of the utterances of the main character. In presenting the data analysis, descriptive qualitative methods were utilized to address the problems of this study. Following the data collection, the mixed method and reducing technique were used in analyzing the data in this study. The theory applied in this study is the theory of language disorder proposed by Carroll (2008), and the theory of language therapy proposed by Beukelman (2013), Scarpa (2013), and Adams (2005). Considering the outcomes of this study, the main character, Tyson Hollerman experiences two types of language disorder, namely expressive and receptive language disorder. From this study, there were 15 data found which indicated the presence of language disorders in Tyson. The 15 data consist of 8 data as expressive disorders and 7 data found as receptive language disorders. Furthermore, based on Tyson’s condition, he was provided with various types of language therapies such as Cognitive Behavioral Therapy, Augmentative and Alternative Communication (AAC) and Pragmatic Language Therapy to address his language disorder.